2020
DOI: 10.1186/s12889-020-8302-z
|View full text |Cite|
|
Sign up to set email alerts
|

Health system factors influencing uptake of Human Papilloma Virus (HPV) vaccine among adolescent girls 9-15 years in Mbale District, Uganda

Abstract: Background: Globally, cervical cancer is the fourth most common cancer in women with more than 85% of the burden in developing countries. In Uganda, cervical cancer has shown an increase of 1.8% per annum over the last 20 years. The availability of the Human Papillomavirus (HPV) vaccine presents an opportunity to prevent cervical cancer. Understanding how the health system influences uptake of the vaccine is critical to improve it. This study aimed to assess how the health systems is influencing uptake of HPV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 30 publications
4
33
1
Order By: Relevance
“…However, there seems to be variations in adequacy of cold-chain capacity and infrastructure between districts. Nabirye et al, found a fully functioning cold chain infrastructure in Eastern Uganda, which was attributed to the revamp supported by development partners in preparation for the introduction of other new childhood vaccines [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there seems to be variations in adequacy of cold-chain capacity and infrastructure between districts. Nabirye et al, found a fully functioning cold chain infrastructure in Eastern Uganda, which was attributed to the revamp supported by development partners in preparation for the introduction of other new childhood vaccines [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, disrespectful behavior frightened some of the girls to the point of leaving the health facilities without being vaccinated. Disrespectful behavior of some health professionals has been reported as a major reason for drop out from a childhood immunization program in Ethiopia [ 48 ] and a key barrier to HPV vaccination in Eastern Uganda [ 13 ]. Our findings highlight the importance of working towards respectful provision of national vaccination services in general in order to improve completion of vaccine doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to a study on cervical cancer screening and acceptability of HPV vaccine among women in Kilimanjaro [49]. Although great support has been established since HPV vaccines have been available since 2006/2007 to promote and educate women globally and especially in LMICs [50], the WHO's recommendation on the HPV vaccine is that in order to achieve the much needed high levels of HPV acceptability, there is urgent need to conduct campaigns to create awareness and provide more accessibility [6,34,51].…”
Section: Integration With Prior Work Implications Transferability and Contribution To The Fieldmentioning
confidence: 99%
“…However, vaccine uptake remains suboptimal globally. This has been associated with low levels of vaccine awareness [32][33][34]. There are many factors that lead to poor compliance to the HPV vaccination program which in turn highly contribute to the failure of vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%